Evaluation of post-contamination survival and persistence of applied attenuated E. coli O157:H7 and naturally-contaminating E. coli O157:H7 on spinach under field conditions and following postharvest handling. (February 2019) - Gutiérrez-Rodríguez, Eduardo; Gundersen, Amy; Sbodio, Adrian; Koike, Steven; Suslow, Trevor V.
Abstract: This study determined the variability in population uniformity of an applied mixture of attenuated E. coli O157:H7 ( attEcO157) on spinach leaves as impacted by sampling mass and detection technique over spatial and temporal conditions. Opportunistically, the survival and distribution of naturally contaminating pathogenic E. coli O157:H7 ( Ec O157), in a single packaged lot following commercial postharvest handling and washing, was also evaluated. From the main study outcomes, differences in the applied inoculum dose of 100-fold, resulted in indistinguishable population densities of approximately Log 1.1 CFU g −1 by 14 days post-inoculation (DPI). Composite leaf samples of 150 g and the inclusion of the spinach petiole resulted in the greatest numerical sensitivity of detection of attEcO157 when compared to 25 and 150 g samples without petioles (P < 0.05). Differences in population density and protected-site survival and potential leaf internalization were observed between growing seasons and locations in California (P < 0.05). A Double Weibull model best described and identified two distinct populations with different inactivation rates of the inoculated attEcO157 . Linear die-off rates varied between 0.14 and 0.29 Log/Day irrespective of location. Detection of Ec O157- stx 1-negative and stx2 -positive, resulting from a natural contamination event, was observed in 11 of 26 quarantined commercial units of washed spinach by applying the 150 g sample mass protocol. The capacity to detect Ec O157 varied between commercial test kits and non-commercial qPCR. Our findings suggest the need for modifications to routine pathogen sampling protocols employed for lot acceptance of spinach and other leafy greens. Highlights: Even homogeneous contamination events result in heterogeneous bacterial survival. Differences in inoculum doses of 100-fold resulted in equal population densities. Detection of Ec O157 varied between commercial test kits and non-commercial qPCR. Leaf samples of 150 g including leaf petioles increased the detection of EcO157. Probable leaf internalization was observed between growing seasons and locations.